Digital ecosystems as social institutions: exploring the role of consumption through four research streams of digital ecosystems. Issue 1 (11th August 2022) - Dulsrud, Arne; Bygstad, Bendik
Abstract : The growth of global digital ecosystems such as Google, Apple and Uber has led to radical changes in economic activity, work and consumption. It has also challenged established economic, social and organisation theory, which has clear limitations in understanding these phenomena. The discourses on these topics are conducted in various arenas, which are not linked, and conceptualise digital ecosystems differently. What kind of theoretical object is this? And what is the role of consumption in digital ecosystems? To investigate these issues, we conducted an investigation in two steps. First, we performed a focused and a comparative analysis of the research on platforms and digital ecosystems. We identified four research streams: the political, the economic, the technological, and the social and cultural. In the second step, we explored a typology of the role of consumption in the four streams, that is, the position in the ecosystem, the consumer agency and the currency of exchange. We associated the consumer as the critical actor of digital ecosystems, because the impact of digital ecosystem development hinges on the way in which consumers perform, accept and integrate the technology into their everyday lives. Our findings highlight that the relationship between consumption and digital technology is multifaceted and non-deterministic.